Right hepatic venous system variation in living donors: a three‐dimensional CT analysis. Issue 9 (26th April 2020) - Watanabe, A.; Yoshizumi, T.; Harimoto, N.; Kogure, K.; Ikegami, T.; Harada, N.; Itoh, S.; Takeishi, K.; Mano, Y.; Yoshiya, S.; Morinaga, A.; Araki, K.; et al.
Abstract : Background: The right hepatic venous system consists of the right hepatic vein (RHV) and inferior RHVs (IRHVs). When the right posterior section is used as a graft for liver transplantation, understanding variations and relationships between the RHV and IRHVs is critical for graft venous return and hepatic vein reconstruction. This study aimed to evaluate variations in the hepatic veins and the relationships between them. Methods: The medical records and CT images of patients who underwent hepatectomy as liver donors were assessed retrospectively. The relationship between the veins was evaluated by three‐dimensional CT. Results: The configuration of the posterior section was classified into one of eight types based on the RHV and IRHVs in 307 patients. Type 1a (103 of 307), type 1b (139 of 307) and type 2a (40 of 307) accounted for 91·9 per cent of the total. The diameter of the RHV extending towards the inferior vena cava had a significant inverse correlation with that of the IRHV ( r 2 = –0·615, P < 0·001). Type 1a, which had no IRHVs, had the RHV with the largest diameter; conversely, type 2a, which had a large IRHV, had the RHV with the smallest diameter. Conclusion: The hepatic venous system of the right posterior section was classified into eight types, with an inverse relationship between RHV and IRHV sizes. This information is useful for segment VII resection or when the right liver is used as a transplant graft. Abstract : This study aimed to clarify variations in the right hepatic vein and inferior right hepatic veins, and to evaluate the relationship between them quantitatively. Understanding the venous configuration can help ensure safe and effective surgery during living donor liver transplantation or hepatectomy. Roadmap for safe surgery Abstract : Antecedentes: El sistema venoso hepático derecho consiste en la vena hepática derecha ( right hepatic vein, RHV) y las RHVs inferiores (IRHVs). Cuando se utiliza la sección posterior derecha hepática como injerto para el trasplante hepático, es fundamental conocer las variaciones e interrelaciones entre la RHV y las IRHVs para el retorno venoso del injerto y la reconstrucción de la vena hepática. El objetivo de este estudio fue determinar las variaciones en las venas hepáticas y sus interrelaciones. Métodos: Se evaluaron retrospectivamente las historias clínicas y las imágenes de la tomografía computarizada de los pacientes que se sometieron a una hepatectomía como donantes vivos para trasplante hepático. La interrelación entre las venas se evaluó mediante imágenes de CT tridimensional. Resultados: La configuración de la sección posterior clasificó a 307 pacientes en base a la RHV y a las IRHVs. Se clasificaron en 8 tipos, de los cuales el Tipo 1a (103/307), el Tipo 1b (139/307) y el Tipo 2a (40/307) representaron el 92% del total. El diámetro de la RHV que se extiende hacia la vena cava inferior presentó una correlación inversa significativa con la de las IRHV (r2: −0, 632, P < 0, 0001). El diámetro mayor de la RHV se observó en el Tipo 1a, que no presentaba IRHVs; por el contrario, el diámetro más pequeño se observó en el Tipo 2a que presentaba una IRHV grande. Conclusión: El sistema venoso hepático de la sección posterior derecha se clasificó en 8 subtipos con una relación inversa entre los tamaños de la RHV y las IRHV. Esta información es útil cuando se practica una resección del segmento 7 o cuando se utiliza el hígado derecho como injerto para el trasplante.